ANALISIS KEMISKINAN DI SEKTOR PERTANIAN (Studi Kasus Komoditas Padi di Kabupaten Malang) - Muhamad Imam Syairozi (Media Ekonomi, 2020)
Identifying factors inhibiting the revitalization of the agricultural sector in Malang Regency and Arranging efforts to revitalize the agricultural sector in accelerating poverty reduction in Malang Regency. The research approach that will be carried out in answering the problem is descriptive quantitative. The discussion will refer to the results of field observations which are then presented systematically and factual with the object of research in subdistricts in Malang Regency in the period 2015 to 2014. Several methods were then used data analysis to answer the problems that have been formulated. Strategies are carried out in order accelerating poverty reduction in Malang Regency, namely the construction of irrigation facilities by increasing budget allocation, empowerment and strengthening of farmer institutions, provision of rice seeds and fertilizers through strengthening farmer groups and development or creation of new technology.